2000
DOI: 10.1007/bf02439255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous ATP on cardiac activity in rats

Abstract: In vivo effects of exogenous ATP on cardiac activity were studied on adult rats. Intravenous administration of ATP produced a positive chronotropic effect, but did not affect the stroke volume. This was due to activation of type II purine receptors, rather than due to the influence of ATP hydrolysis products, since P1 receptor agonist adenosine was ineffective. The blockade of beta-adrenoceptors and muscarinic receptors did not modify the positive chronotropic effect of ATP, which indicated that this action wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…By using magnetic resonance techniques, Pluim et al [34] showed that heart rate variability is significantly correlated with high-energy phosphate metabolism in trained and sedentary subjects. In fact, intravenous administration of ATP produced a 4-fold increase in the variability of heart rate typically indicating an activation of the parasympathetic myocardial regulation [35]. Therefore, an extra energy cost of skeletal muscle to the detriment of cardiac activity or a disruption of sarcolemmal ATP-sensitive K + channels [36] induced by supramaximal exercise may provoke a delayed cardiac tone response.…”
Section: Discussionmentioning
confidence: 99%
“…By using magnetic resonance techniques, Pluim et al [34] showed that heart rate variability is significantly correlated with high-energy phosphate metabolism in trained and sedentary subjects. In fact, intravenous administration of ATP produced a 4-fold increase in the variability of heart rate typically indicating an activation of the parasympathetic myocardial regulation [35]. Therefore, an extra energy cost of skeletal muscle to the detriment of cardiac activity or a disruption of sarcolemmal ATP-sensitive K + channels [36] induced by supramaximal exercise may provoke a delayed cardiac tone response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments showed that intravenous infusion of ATP produces a positive chronotropic effect on the heart, but does not change stroke volume (SV). This effect is associated with activation of P2 purinoceptors, but not with the influence of products formed during ATP hydrolysis, because P1 receptor agonist adenosine was ineffective [1].…”
mentioning
confidence: 99%